Biuletyn Dolnośląski . miesięcznik niezależny, no. 50, 1983 - Morawiecki, Kornel; Waszkiewicz, Jan; Ewaryst, Jan; Twaed.owski, Marek; Gorbanevskaja, Natal'ja; Prus, Marcin; Besançon, Alain; Gwiazda, Andrzej; Wierzyński, Michał; Jaworski, Rafał; Teliga, Józef; Myślecki, Wojciech; et al. (Agencja Informacyjna Solidarności Walczącej, 1983)
Print run: 2000-10000 copies